The influence of a teachers' professional development programme on primary school pupils' understanding of and attitudes towards sustainability. Issue 7 (15th February 2021) - Murphy, Clíona; Mallon, Benjamin; Smith, Greg; Kelly, Orla; Pitsia, Vasiliki; Martinez Sainz, Gabriela
Abstract: Transformative teacher education can support educational experiences which provide the opportunity for pupils to develop the knowledge, skills and attitudes to contribute towards tackling the significant sustainability issues with which we are faced. It is argued that for professional development programmes to be effective they need to improve pupil learning as well as transform teachers' classroom practice. This paper utilises a mixed-methods design to investigate the influence of an innovative sustainability and science education focused programme of professional development, on primary pupils' (ages 8 − 11 years) understanding of and attitudes towards sustainability. The findings reveal that primary teachers' participation in the programme and implementation of the associated pedagogies afforded pupils the opportunity to: deepen their understanding of key sustainability issues and the potential actions that may be undertaken; further develop positive attitudes towards sustainability albeit alongside understanding the magnitude of the challenge that presents; begin the early development of particular sustainability competencies.